Perencanaan dan Pengorganisasian Layanan Bimbingan Manasik Haji: Studi Kasus pada KBIH Al-Bayt Tours Demak - Yasfin, Moh. Anwar (Tadbir: Jurnal Manajemen Dakwah, 2025)
This study aims to examine the planning and organization of hajj guidance services at KBIH Al-Bayt Tours Demak, focusing on the effectiveness of planning, structured organization, and the application of andragogy methods in guidance services. Using a qualitative approach with field research methods, data were collected through observation, in-depth interviews, and documentation of guidance activities. Data analysis was carried out descriptively based on the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that the planning of guidance services at KBIH Al-Bayt Tours Demak was carried out effectively and systematically, allowing pilgrims to understand and prepare for the hajj optimally. The organization of guidance was carried out with a clear structure, proper division of tasks, and good coordination. In addition, the andragogy approach used in guidance includes participatory and practice-oriented learning methods, in accordance with the characteristics of adult learning. This study provides suggestions for KBIH Al-Bayt Tours to continue to improve the quality of guidance services by conducting periodic evaluations and updating guidance materials and methods. The use of technology and interactive learning media can be an alternative to increase congregation involvement in learning.